2019
DOI: 10.1016/j.jcpa.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Rhinitis in a Horse due to Mycobacterium intracellulare Infection

Abstract: Mycobacterial infections in horses are uncommon, but are caused most frequently by Mycobacterium bovis of the Mycobacterium tuberculosis complex or Mycobacterium avium of the M. avium complex. Disease caused by Mycobacterium intracellulare, the second most common species within the M. avium complex, has not been reported in horses to date. Mycobacteriosis in horses most often presents as enteric, pulmonary, or rarely, systemic disease. Here we report a case of M. intracellulare infection in a horse presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Granulomatous diseases of the nose and paranasal sinuses represent an uncommon but clinically important and potentially lethal group of disorders encountered in otolaryngologic practice ( Muller et al., 2021 ; Vail et al., 2019 ). There is a pressing need for a knowledge-driven approach that can facilitate high index of suspicion with timely diagnosis, followed by medical and surgical management to avoid any destruction to the nose, paranasal sinuses, orbit and even the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulomatous diseases of the nose and paranasal sinuses represent an uncommon but clinically important and potentially lethal group of disorders encountered in otolaryngologic practice ( Muller et al., 2021 ; Vail et al., 2019 ). There is a pressing need for a knowledge-driven approach that can facilitate high index of suspicion with timely diagnosis, followed by medical and surgical management to avoid any destruction to the nose, paranasal sinuses, orbit and even the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Although many diseases affect the nose, most of them are granulomatous-a condition associated with granuloma formation (a collection of histiocytes made up of modified macrophages/epithelioid cells), often surrounded by T-lymphocytes, multinucleated giant cells & sometimes associated with central necrosis ( Vail et al., 2019 ). Granuloma is formed, when the immune system fails to eliminate foreign bodies and attempts to wall off these substances ( Wheeler and Woroniecki, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pulmonary disease is the most frequent form of NTM in adult humans with MAC, M. kansasii , M. abscessus , and M. fortuitum being the most common NTM pulmonary pathogens in the United States [ 31 , 32 ]. In horses, a case of granulomatous rhinitis associated with infection with M. intracellulare , an uncommon species of MAC, was recently reported in Texas (USA) [ 24 ]. The horse was a 22-year-old Quarter Horse gelding with a 2-month history of unilateral mucopurulent nasal discharge.…”
Section: Clinical Manifestation Of Ntmmentioning
confidence: 99%
“…In addition, numerous acid-fast bacilli were identified on acid-fast stain. The PCR amplification revealed that the pathogen shared 98% of identity with M. intracellulare [ 24 ]. This report indicates that NTM should be considered a differential diagnosis for horses with nasal masses and granulomatous rhinitis.…”
Section: Clinical Manifestation Of Ntmmentioning
confidence: 99%
See 1 more Smart Citation